CDA-OPTIMUM DESIGN FOR PARAMETER ESTIMATION, MINIMIZING THE AVERAGE VARIANCE AND ESTIMATING THE AREA UNDER THE CURVE - Abd El-Monsef, Mohamed; El-Sobky, Sally (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
The aim of this paper is to introduce a new compound optimum design named CDA, by combining the C-optimality, D-optimality, and A-optimality together. The significance of the proposed compound gains from that it can be used for parameter estimation, minimizing the average variance and model estimation simultaneously.